Arachniodes breviaristata (Dryopteridaceae): a new species from Jiangxi, China - Wei, Hong-Jin; Le, Xin-Gui; Chen, Bin (Phytotaxa, 2023)
Arachniodes breviaristata, a new species of Dryopteridaceae from Jiangxi, China, is described and illustrated. The new species is most similar to A. exilis in terms of pinnule shape and serrature form, but can be easily recognized by its lamina shape, degree of shrinkage of the lamina apex and relative length of basiscopically basal pinnules of the lowest pinnae. The new species is suggested to be classified as Critically Endangered (CR) following IUCN Red List Criteria.